2013
DOI: 10.1002/dneu.22097
|View full text |Cite
|
Sign up to set email alerts
|

The effects of prenatal stress on Alpha4 Beta2 and Alpha7 hippocampal nicotinic acetylcholine receptor levels in adult offspring

Abstract: Prenatal stress in humans is associated with psychiatric problems in offspring such as anxiety, depression, and schizophrenia. These same illnesses are also associated with neuronal nicotinic acetylcholine receptor (nAChR) dysfunction. Despite the known associations between prenatal stress exposure and offspring mental illness, and between mental illness and nAChR dysfunction, it is not known whether prenatal stress exposure impacts neuronal nAChRs. Thus, we tested the hypothesis that maternal stress alters th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 58 publications
1
22
0
Order By: Relevance
“…For example, perinatal choline is capable of increasing nAChRs in mouse strains with low levels of hippocampal nAChRs [27, 54]. Given that we have recently found that prenatal stress alters hippocampal levels of both alpha4 beta2* and alpha7* nAChRs [19], it is plausible that prenatal choline counteracts the impact of prenatal stress by maintaining normative levels of nAChRs in the hippocampus. Studies are currently underway to compare the levels of hippocampal nAChRs in prenatally stressed animals gestated on control or choline supplemented diet.…”
Section: 0 Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, perinatal choline is capable of increasing nAChRs in mouse strains with low levels of hippocampal nAChRs [27, 54]. Given that we have recently found that prenatal stress alters hippocampal levels of both alpha4 beta2* and alpha7* nAChRs [19], it is plausible that prenatal choline counteracts the impact of prenatal stress by maintaining normative levels of nAChRs in the hippocampus. Studies are currently underway to compare the levels of hippocampal nAChRs in prenatally stressed animals gestated on control or choline supplemented diet.…”
Section: 0 Discussionmentioning
confidence: 99%
“…Furthermore, cholinergic abnormalities are associated with anxiety and depression in humans [1318]. In rodents, prenatal stress alters levels of both alpha7* and alpha4 beta2* hippocampal nAChRs [19], and alters stress-dependent hippocampal cholinergic function in adulthood [20], suggesting that the effects of prenatal stress on anxiety-related behaviors may be driven by altered development of the hippocampal cholinergic system.…”
Section: Introductionmentioning
confidence: 99%
“…First support for causality has recently been obtained by the observation that these cognitive impairments can be prevented by perinatal administration of the α7nACh receptor agonist choline [23]. Notably, prenatal stress causes α7nACh receptor abnormalities in the offspring [68,69], and prenatal dietary choline supplementation has been shown to have positive behavioral effects in a variety of informative animal models [7072]. It is therefore tempting to speculate that the acute effect of prenatal stress on KYNA described here, especially if accompanied and potentially exacerbated by KP abnormalities caused by infections or other immune activations during pregnancy [32,53,7375], may be directly related to behavioral impairments later in life and the etiology of major brain diseases.…”
Section: Discussionmentioning
confidence: 99%
“…These discrepancies may be due to strain effects, indeed alterations in brain-derived neurotrophic factor (BDNF), glucocorticoid receptors and nicotinic receptor expression in the hippocampus following prenatal stress in rats are highly dependent on background strain (Neeley et al 2011). Given that both glucocorticoid receptor expression (Bielas et al 2014), BDNF expression (Hill 2012a) and 7 nicotinic receptor expression (Schulz et al 2013) are sex-dependently M a n u s c r i p t 14 regulated during brain development, strain differences in the expression of these developmental proteins would then affect the sex-specific response to stress.…”
Section: Prenatal Stress Modelmentioning
confidence: 97%